Fracture risk prediction on children with osteogenesis imperfecta subjected to loads under activity of daily living - Wanna, S B C; Basaruddin, Khairul Salleh; Mat Som, Mohd Hanafi; Sulaiman, Abdul Razak; Awang, Mohd Shukrimi; Mohamad Khan, Shah Fenner Khan; Abdul Majid, Mohd Shukry; Mohd Jamir, Mohd Ridzuan (Institute of Physics Publishing, 2018)
Children with Osteogenesis Imperfecta (OI) often vulnerable to fracture even on their daily basic tasks. The unpredicted fracture leads to intramedullary surgery. This study aims to investigate the fracture risk in children with OI in daily basic tasks including standing, walking, and jumping. Ten models of OI finite elements were reconstructed based on the radiography CT image of enrolled OI patients. An actual body weight of OI patient was used as the main force acting vertically towards the femoral head and then the fracture risk was observed. In standing and walking configuration, all ten OI models were found able to sustain the acted load. Whereas in jumping configuration, all OI models suffered to become fracture. Early prediction of fracture risk could help medical personnel and OI patients from fall or injury.